2013
DOI: 10.1002/hec.2904
|View full text |Cite
|
Sign up to set email alerts
|

Waiting Times and Socioeconomic Status. Evidence From Norway

Abstract: We investigate whether socioeconomic status, measured by income and education, affects waiting time when controls for severity and hospital-specific conditions are included. We also examine which aspects of the hospital supply (attachment to local hospital, traveling time, or choice of hospital) matter most for unequal treatment of different socioeconomic groups. The study uses administrative data from all elective inpatient and outpatient stays in somatic hospitals in Norway. The main results are that we find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 16 publications
2
28
0
Order By: Relevance
“…6 See, for instance, Cookson et al (2016) for a review of the literature on socio-economic inequalities in healthcare in England, which reveals a large body of research in the fields of health service and social medicine, mainly focusing on small-area (neighbourhood) variations. 7 There are also recent studies on the relationship between SES and waiting times, as a measure of access to health care; see, for example, Kaarboe and Carlsen (2014) and Monstad, Engesaeter, and Espehaug (2014). 8 A similar finding is reported for Norway by Grasdal and Monstad (2011).…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…6 See, for instance, Cookson et al (2016) for a review of the literature on socio-economic inequalities in healthcare in England, which reveals a large body of research in the fields of health service and social medicine, mainly focusing on small-area (neighbourhood) variations. 7 There are also recent studies on the relationship between SES and waiting times, as a measure of access to health care; see, for example, Kaarboe and Carlsen (2014) and Monstad, Engesaeter, and Espehaug (2014). 8 A similar finding is reported for Norway by Grasdal and Monstad (2011).…”
mentioning
confidence: 58%
“…Individuals can switch GP (at most twice per calender year) within the municipality. 12 The GPs can decide the size of their list, but are required to have at least 500 patients and not more than 2500 patients. If a GP's list is full (closed), then the GP can potentially turn down new patients.…”
Section: Institutional Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, the only other previous study using a general indicator was a cross-sectional study using individual-level data on men aged ≥ 67 years from Norway in 2004/5, which found very little evidence of socioeconomic differences in waiting time after adjusting for all primary and secondary diagnoses, severity and hospital supply. 167 By contrast, previous disease-specific studies have generally found pro-rich inequality in waiting time for publicly funded inpatient hospital treatment in a range of high-income countries with universal health systems. 168,169 Previous disease-specific studies have also found a trend of reducing socioeconomic inequality in the English NHS during the 2000s, for a handful of common non-emergency hospital procedures such as hip replacement, knee replacement cataract, heart bypass and coronary angioplasty.…”
Section: Waiting Timementioning
confidence: 89%
“…Several recent studies examine the relationship between waiting times and socioeconomic status (Carlsen and Kaarbøe, 2012;Kaarbøe and Carlsen, 2014;Johar et al, 2013;Siciliani and Verzulli, 2009). All of these studies find higher income and education to be associated with lower waiting times for public health services.…”
Section: Detecting Discrimination In Health Carementioning
confidence: 97%